Ursodiol in Patients with Parenteral Nutrition–Associated Cholestasis - Btaiche, Imad F. (2007)
OBJECTIVE To review the role of ursodeoxycholic acid (ursodiol) in treating parenteral nutrition–associated cholestasis (PNAC). DATA SOURCES A MEDLINE (1950–May 2007) search was performed using the key terms parenteral nutrition, cholestasis, ursodeoxycholic acid, and ursodiol. STUDY SELECTION AND DATA EXTRACTION All English-language articles that evaluated the safety and efficacy of ursodiol for PNAC were included in this review. DATA SYNTHESIS The benefits of exogenous ursodiol administration in the treatment of cholestasis can be explained by its alteration of effects on bile composition and flow and provision of cytoprotective, membrane stabilizing, and immunomodulatory effects. Two animal studies, 2 case reports, and 6 human studies (2 prospective and 3 retrospective pediatric studies, 1 adult prospective study) evaluated the efficacy of ursodiol in patients with PNAC. Ursodiol 10–30 mg/kg/day in children and 10–15 mg/kg/day in adults administered in 2–3 doses improved the biochemical and clinical signs and symptoms of PNAC. However, short-term improvement in biochemical parameters may not necessarily predict the outcome of PNAC patients. At recommended doses, ursodiol may not be effective in patients with short bowel syndrome or in those with resected terminal ileum because of reduced ursodiol absorption. Studies supporting the efficacy of ursodiol in treatment of PNAC are limited by small sample size, absence of randomization and controls, short duration, and lack of accountancy to confounding variables. Large, prospective, randomized, placebo-controlled, long-term follow-up studies evaluating the efficacy and optimal dosing and duration of ursodiol therapy for PNAC are not yet available. CONCLUSIONS Ursodiol may improve the biochemical signs and clinical symptoms of PNAC. However, optimal dosing, timing, duration of therapy, and long-term effects on PNAC outcome and prognosis require further studies.